Selecting the power electronic interface for a supercapattery based energy storage system - Klumpner, Christian; Asher, Greg; Chen, George Z. (2009)
This paper presents the initial investigations in selecting the topology of the power electronic interface for an energy storage system for power levelling applications based on a novel storage device, the supercapattery. The particularities of the supercapattery device are summarized leading to a multistage power converter structure. A review of the two stage DC/DC converter structure to interface with the supercapattery and of various DC/AC inverters and conversion techniques suitable for connection to a medium voltage and high power AC grid, is given. Simulation results prove the capability of the power electronic interface to control independently and fast the active and reactive power flow which are vital in power peak leveling and power grid stabilization.